Edwardian Bloomsbury - Rosenbaum, S. author. aut Link
XV, 559 p.
Keywords: 'This is the second volume of a formidable enterprise, and part of a series of publications by the same author that may entitle him to the position as the leading scholar of the Bloomsbury Group...Rosenbaum has managed to write with freshness and insight about Forster's novels, no matter how much they have been analyzed before...The next volume will deal with the effect of that exhibition upon the Group's writing and much more, I am sure, of its early literary history. The work is eagerly awaited.' - Peter Stanksy, English Literature in Transition 1880-1920 Edwardian Bloomsbury is a continuation of the early literary history of the Bloomsbury Group begun with Victorian Bloomsbury, but it can also be read independently as an account of the Group's interrelated writings during the first decade of the twentieth century.